Preparation of mesoporous hard carbon anode materials by nitrogen doping of biomass to enhance the specific capacity of sodium ion adsorption - Meng, Wei; Gao, Yinyi; Zhu, Kai; Cao, Dianxue (Journal of electroanalytical chemistry (Lausanne, Switzerland), 2025)
This study synthesized a hard carbon anode material (HC-N1300) with hierarchical micro/mesoporous structure through biomass-derived nitrogen doping, aiming to explore its application in sodium-ion batteries (SIB). Structural characterization reveals that HC-N1300 possesses well-developed micro/mesopores, which significantly shorten the diffusion pathways for sodium ions (Na+). Compositional analysis further demonstrates an increased ratio of pyridinic-N to pyrrolic-N configurations, providing abundant electrochemically active sites. These synergistic structural and compositional advantages collectively enhance the adsorption capability in the slope region. In half-cell evaluations, the HC-N1300 delivered an initial discharge capacity of 486 mAh g−1 at 0.1 A g−1 with a reversible capacity of 330 mAh g−1. Remarkably, it maintained 88.5 % capacity retention after 1000 cycles at 0.5 A g−1. Mechanistic analysis revealed that nitrogen doping plays a crucial role in pore formation during carbonization. The hierarchical porous architecture not only increases active sites but also facilitates rapid Na+ diffusion, thereby effectively improving both plateau capacity and rate capability. This work provides valuable insights for designing high-performance anode materials for SIB. •Precision microstructure engineering via biomass-derived nitrogen doping. A hierarchical micro-mesoporous network (pore size distribution: 2–110 nm) and a nitrogen conformational shift (elevated ratio of pyridine-N and pyrrolidine-N) was constructed through nitrogen doping, enabling ultra-short Na+ diffusion pathways and exceptionally high active site density.•Breakthrough electrochemical performance. 486 mAh g−1 initial discharge capacity at 0.1 A g−1 with 330 mAh g−1 reversible capacity. 88.5 % capacity retention after 1000 cycles at 0.5 A g−1 (ultralow decay rate of 0.0115 % per cycle). Superior rate capability: maintains 236 mAh g−1 at 2 A g−1 (71 % retention of 0.1 A g−1 capacity)•First-established dual-function mechanism of nitrogen doping. Pore engineering: nitrogen-induced N2 release creates 3D interconnected ion transport channels during carbonization. Interlayer spacing optimization: expanded graphitic interlayer spacing to 0.41 nm (22.4 % larger than graphite), significantly reducing Na+ intercalation energy barriers by 34 %.